Eksperimen Pembelajaran Matematika Melalui Strategi Problem Based Learning Dan Discovery Learning Berbasis Ict Terhadap Hasil Belajar Ditinjau Dari Kemampuan Komunikasi Matematis Siswa Kelas VII - Haryanti, Fitri, Prof. Dr. Budi Murtiyasa, M.Kom (2017)
The research is a conducted to know: (1) the effect of Strategy the Problem Based Learning dan Discovery Learning based ICT on student learning outcomes, (2) the effect of mathematics communication ability on student learning outcomes, (3) the interaction between learning strategy and mathematics communication ability on student learning outcomes. The research experimental type is quasi-experimental design. The population of research is all of the 7th grades students of SMP Negeri 2 Banyudono in academic years of 2016/2017. Samples of this research is class VII B and VII C. The sampling technique is cluster random sampling. The collection data technique used the method of test, questionnaire, and documentation. Technique of analyzing data used analysis of variance two different cells. The research result with α = 5% show that: (1) there are effect of Strategy the Problem Based Learning dan Discovery Learning based ICT on student learning outcomes i.e Fobs = 5,0757 > Ftable = 3,9886, (2) there are effect of mathematics communication ability on student learning outcomes i.e Fobs = 3,9022 > Ftable = 3,1381, (3) thre are no interaction between learning strategy and mathematics communication ability on student learning outcomes i.e Fobs = 2,5902 > Ftable = 3,1381. Keywords: Problem Based Learning based ICT, Discovery Learning based ICT, mathematics communication ability, student learning outcomes